Personal characteristics supporting Paralympic athletes` self-realization in sports - Kokun, O.; Serdiuk, L.; Shamych, O. (Journal of Human Sport & Exercise, 2021)
The purpose of this study was to investigate the personal characteristics supporting Paralympic athletes` self-realization in sports. The study involved 106 members of the Paralympic and Deaflympic teams of Ukraine (16-53 year-old, the average age of 28.3 ± 7.2 years; 84 men with the average age of 27.7 ± 6.7 years and 22 women with the average age 30.3 ± 8.3 years) in different sports (football, fencing, power-lifting, sitting volleyball, judo, canoeing in pairs, swimming). It is determined that the most important personal factor supporting Paralympic athletes` self-realization in sports is their psychological hardiness. Their self-efficacy, capacity for self-organization of their activities and psychological well-being can also be considered as significant personal characteristic necessary for their self-realization in sports.